1996
DOI: 10.1148/radiology.201.2.8888219
|View full text |Cite
|
Sign up to set email alerts
|

Focal liver lesions: characterization with triphasic spiral CT.

Abstract: Triphasic liver CT enables characterization of a wide range of focal liver lesions, including the benign liver lesions that occur most frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0
8

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 32 publications
7
84
0
8
Order By: Relevance
“…When all lesions exhibiting this enhancement pattern were considered, malignancy was predicted with a PPV of 90% and specificity of 94%. These findings are similar to those in the series of Van Leeuwen and colleagues (2), who found that a hyperattenuatingring in the arterial phase was associated with malignancy in all cases. It is important to bear in mind, however, that not all ring-enhancing lesions are malignant; for example, as noted in one patient in our series, this feature may also be noted with abscesses (3).…”
Section: Figure 13supporting
confidence: 91%
See 2 more Smart Citations
“…When all lesions exhibiting this enhancement pattern were considered, malignancy was predicted with a PPV of 90% and specificity of 94%. These findings are similar to those in the series of Van Leeuwen and colleagues (2), who found that a hyperattenuatingring in the arterial phase was associated with malignancy in all cases. It is important to bear in mind, however, that not all ring-enhancing lesions are malignant; for example, as noted in one patient in our series, this feature may also be noted with abscesses (3).…”
Section: Figure 13supporting
confidence: 91%
“…Bolus or arterial phase scans were found to be advantageous in small lesions that enhanced to a greater degree than the adjacent liver (positive contrast)(5). They also found that arterial phase helical CT of the liver improved the detection of some small hepatic neoplasms when compared with portal venous scanning alone (2). In the study conducted by Leeuwen et al, 1996 parenchymal enhancement of the liver in the arterial phase was found to be well below than that in the portal phase.…”
Section: Figure 13mentioning
confidence: 95%
See 1 more Smart Citation
“…Its ability to acquire images of the entire organ within a single breath-hold eliminates the problem of respiratory misregistration, thus allowing confident detection of subcentimeter lesions, and facilitating optimal contrast delivery. 1,2 The rapid scan time also allows helical CT to capture the liver during both the arterial phase (20-30 seconds after the beginning of contrast administration) and venous or portal phase of contrast perfusion (60-70 seconds after contrast administration). 3,4 The advantages of this ability are obvious.…”
Section: Photon (Ct)mentioning
confidence: 99%
“…Kolorektale Lebermetastasen sind zu 85-90 % hypovaskularisiert und stellen sich daher in der kontrastmittelverstärkten CT hypodens dar. Der Kontrast zum umgebenden Gewebe ist aufgrund der dualen Blutversorgung der Leber in der portalvenösen Phase am ausgeprägtesten [28,29]. Da 10-15 % der kolorektalen Lebermetastasen hypervaskularisiert sind, muss auch immer eine arterielle Phase angefertigt werden.…”
Section: Computertomographieunclassified